Thriving at Work and Perceived Overqualification as Predictors of Employee Career Outcomes - Ghina Amira; Adjeng Mariana Febrianti (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2022)
This study develops and tests a model which views career outcomes from both positive and negative sides, namely career satisfaction and turnover intention. To understand the predictors of career outcomes, researchers posit thriving at work and perceived overqualification as positive and negative antecedents that will influence individual career outcomes purpose of this study is to understand the influence of thriving at work and perceived overqualification on employee career outcomes, which is seen from career satisfaction and turnover intention. This study is carried out on service company employees in Bandung, West Java. The sampling technique in this study is carried out by simple random sampling, with the final number of samples of 110 respondents. The data collection is done by distributing questionnaires using online platforms to the respondents. The questionnaire items used are measured using a 5-point Likert scale. The data is then processed using multiple linear regression analysis with SPSS 23 software. The results of this study indicate that thriving at work positively influences employee career satisfaction, and negatively influences turnover intention. On the other hand, perceived overqualification negatively impacts career satisfaction and positively influences turnover intention.